A survey of the accuracy of interpretation of intraoperative cholangiograms - Sanjay, Pandanaboyana (Blackwell Publishing Ltd, 2012)
OBJECTIVES: There are few data in the literature regarding the ability of surgical trainees and surgeons to correctly interpret intraoperative cholangiograms (IOCs) during laparoscopic cholecystectomy (LC). The aim of this study was to determine the accuracy of surgeons' interpretations of IOCs. METHODS: Fifteen IOCs, depicting normal, variants of normal and abnormal anatomy, were sent electronically in random sequence to 20 surgical trainees and 20 consultant general surgeons. Information was also sought on the routine or selective use of IOC by respondents. RESULTS: The accuracy of IOC interpretation was poor. Only nine surgeons and nine trainees correctly interpreted the cholangiograms showing normal anatomy. Six consultant surgeons and five trainees correctly identified variants of normal anatomy on cholangiograms. Abnormal anatomy on cholangiograms was identified correctly by 18 consultant surgeons and 19 trainees. Routine IOC was practised by seven consultants and six trainees. There was no significant difference between those who performed routine and selective IOC with respect to correct identification of normal, variant and abnormal anatomy. CONCLUSIONS: The present study shows that the accuracy of detection of both normal and variants of normal anatomy was poor in all grades of surgeon irrespective of a policy of routine or selective IOC. Improving operators' understanding of biliary anatomy may help to increase the diagnostic accuracy of IOC interpretation.